Characterization and mechanism of seed dormancy in Symplocos paniculata - Tang, Qiaoyu; Chen, Yunzhu; Jiang, Lijuan; Chen, Jingzhen; Li, Changzhu; Zeng, Wenbin; Liu, Qiang; Li, Peiwang (Frontiers in Plant Science, 2024)
Symplocos paniculata is a highly desirable oil species for biodiesel and premium edible oil feedstock. While germplasm preservation and breeding are crucial, the severity of seed dormancy poses a challenge to successful germination. We employed S. paniculata seeds as experimental materials and conducted an investigation into the types and causes of seed dormancy by analyzing the morphology and developmental characteristics of its embryo, exploring the water permeability property of the endocarp, and examining the presence of endogenous inhibitors, aiming to establish a theoretical foundation for overcoming seed dormancy and maximizing germplasm resource utilization. The findings revealed that the seed embryo had matured into a fully developed embryo, and no dormancy in terms of embryo morphology was observed. Upon reaching maturity, the endocarp of seeds undergoes significant lignification, resulting in notable differences in water absorption between cracked and intact seeds. The impermeability of the endocarp is one of the factors contributing to dormancy. The different phases of endosperm extraction exerted varying effects on the germination of Chinese cabbage seeds, with the methanol phase exhibiting the most potent inhibitory effect. The presence of endogenous inhibitors emerged as the primary factor contributing to physiological dormancy in seeds. GC-MS analysis and validation trials revealed that fatty acids and phenolics, including hexadecanoic acid, oxadecanoic acid, and m-cresol, constituted the main types of endogenous inhibitory compounds found within the endosperm. The dormancy of S. paniculata seeds was believed to be a harmonious blend of physical and physiological factors, resulting in an exquisite state of quiescence.Symplocos paniculata is an indigenous deciduous shrub in China, boasting both ecological and economic significance. This remarkable species is also renowned for its fireproof properties, earning it the classification of a national second-class fireproof tree species. Moreover,